2019
DOI: 10.1541/ieejjia.8.23
|View full text |Cite
|
Sign up to set email alerts
|

Simple Harmonics Compensation Method for Smart Charger with Constant DC-Capacitor Voltage-Control for Electric Vehicles in Single-Phase Three-Wire Distribution Feeders

Abstract: This paper discusses harmonic current compensation of the constant dc-capacitor voltage-control (CDCVC)-based strategy for smart charger for electric vehicles (EVs) in single-phase three-wire distribution feeders (SPTWDFs) under distorted load current conditions. The basic principle of the CDCVC-based harmonics compensation strategy under distorted load current conditions is discussed in detail. The instantaneous power flowing into the three-leg pulse-width modulated (PWM) rectifier, which acts as a smart char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…In (4), however, only linear loads were connected in SPTWLVFs. The authors dealt with harmonic current compensation with this CDCVC-based method (5) . Simulation and experimental results confirmed that the balanced and sinusoidal source currents with a unity power factor (PF) in SPTWLVFs were achieved using the CDCVC-based method.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…In (4), however, only linear loads were connected in SPTWLVFs. The authors dealt with harmonic current compensation with this CDCVC-based method (5) . Simulation and experimental results confirmed that the balanced and sinusoidal source currents with a unity power factor (PF) in SPTWLVFs were achieved using the CDCVC-based method.…”
Section: Introductionmentioning
confidence: 99%
“…There are four nodes numbered, 1, 2, 3, and 4, in the SPTWLVF on the secondary side of the PMDT. Three domestic consumers are connected at each node while only one domestic consumer is connected in an SPTWLVF in (4), (5), and (6). The commercial SPTWLVF in Fig.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations